Modes Control of Lamb Wave in Plates Using Meander-Line Electromagnetic Acoustic Transducers - Yinghong Zhang; Zhenghua Qian; Bin Wang (Applied Sciences, 2020)
The multimode and dispersion characteristics of Lamb waves make them difficult to apply to nondestructive evaluation. This paper presents a paired configuration of a meander-line coil electromagnetic acoustic transducer (EMAT) to generate a single-mode symmetric and antisymmetric Lamb wave in aluminum plates. In the paired structure, the bias magnetic field of the EMAT that generates symmetric mode Lamb waves is perpendicular to the plate surface, while the bias magnetic field of the EMAT that generates antisymmetric Lamb waves is parallel to the plate surface. The symmetric and antisymmetric exciting forces generated by these two EMATs are consistent with the dispersion equations of single symmetric and antisymmetric Lamb wave modes, respectively. The numerical simulations and experiments verified that the presented paired configurations of meander-line coil EMATs can effectively control the generation of single-mode Lamb waves at low frequencies.